2016
DOI: 10.1095/biolreprod.116.139204
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine-Mediated Effects of Prolactin Dictate Emergence from Mink Obligate Embryonic Diapause

Abstract: Embryonic diapause is an evolutionary strategy to ensure that offspring are born when maternal and environmental conditions are optimal for survival. In many species of carnivores, obligate embryonic diapause occurs in every gestation. Reciprocal embryo transplant studies indicate that embryo arrest during diapause is conferred by uterine conditions and is due to a lack of specific factors necessary for continued development. In previous studies, global gene expression analysis revealed reduced uterine express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 42 publications
2
47
0
Order By: Relevance
“…These findings suggest that a decline in putrescine causes delayed embryonic development, whereas treatment with putrescine leads to an increase in the rate of embryonic development in C. sphinx. These results thus support a recent study where putrescine treatment was shown to accelerate the development of the delayed embryo in the mink (Fenelon et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings suggest that a decline in putrescine causes delayed embryonic development, whereas treatment with putrescine leads to an increase in the rate of embryonic development in C. sphinx. These results thus support a recent study where putrescine treatment was shown to accelerate the development of the delayed embryo in the mink (Fenelon et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…sphinx . These results thus support a recent study where putrescine treatment was shown to accelerate the development of the delayed embryo in the mink (Fenelon et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…After attaining 80% confluency, the cells were fed with 1% FBS, with or without (control) the test reagents (putrescine and DFMO) for 24 hr. The cells were treated with putrescine 0.5 µM, putrescine 2 µM, and DFMO 10 µM (Fenelon, Banerjee, Lefèvre, Gratian, & Murphy, 2016). All experiments were repeated three to four times with triplicate monolayers of 1 × 10 6 cells.…”
mentioning
confidence: 99%